For any <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>cot</mi><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow></mstyle></math> , vertical asymptotes occur at <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mi>n</mi><mi>π</mi></mstyle></math> , where <math><mstyle displaystyle="true"><mi>n</mi></mstyle></math> is an integer. Use the basic period for <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>cot</mi><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow></mstyle></math> , <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mi>π</mi><mo>)</mo></mrow></mstyle></math> , to find the vertical asymptotes for <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mo>-</mo><mi>cot</mi><mrow><mo>(</mo><mn>11</mn><mi>x</mi><mo>)</mo></mrow></mstyle></math> . Set the inside of the cotangent function, <math><mstyle displaystyle="true"><mi>b</mi><mi>x</mi><mo>+</mo><mi>c</mi></mstyle></math> , for <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>a</mi><mi>cot</mi><mrow><mo>(</mo><mi>b</mi><mi>x</mi><mo>+</mo><mi>c</mi><mo>)</mo></mrow><mo>+</mo><mi>d</mi></mstyle></math> equal to <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> to find where the vertical asymptote occurs for <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mo>-</mo><mi>cot</mi><mrow><mo>(</mo><mn>11</mn><mi>x</mi><mo>)</mo></mrow></mstyle></math> .

Divide each term by <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mn>11</mn><mi>x</mi><mo>=</mo><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Divide <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

Set the inside of the cotangent function <math><mstyle displaystyle="true"><mn>11</mn><mi>x</mi></mstyle></math> equal to <math><mstyle displaystyle="true"><mi>π</mi></mstyle></math> .

Divide each term by <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mn>11</mn><mi>x</mi><mo>=</mo><mi>π</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

The basic period for <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mo>-</mo><mi>cot</mi><mrow><mo>(</mo><mn>11</mn><mi>x</mi><mo>)</mo></mrow></mstyle></math> will occur at <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mfrac><mrow><mi>π</mi></mrow><mrow><mn>11</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math> , where <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mi>π</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math> are vertical asymptotes.

The absolute value is the distance between a number and zero. The distance between <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> is <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

The vertical asymptotes for <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mo>-</mo><mi>cot</mi><mrow><mo>(</mo><mn>11</mn><mi>x</mi><mo>)</mo></mrow></mstyle></math> occur at <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> , <math><mstyle displaystyle="true"><mfrac><mrow><mi>π</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math> , and every <math><mstyle displaystyle="true"><mfrac><mrow><mi>π</mi><mi>n</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math> , where <math><mstyle displaystyle="true"><mi>n</mi></mstyle></math> is an integer.

Cotangent only has vertical asymptotes.

No Horizontal Asymptotes

No Oblique Asymptotes

Vertical Asymptotes: <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mfrac><mrow><mi>π</mi><mi>n</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math> where <math><mstyle displaystyle="true"><mi>n</mi></mstyle></math> is an integer

No Horizontal Asymptotes

No Oblique Asymptotes

Vertical Asymptotes: <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mfrac><mrow><mi>π</mi><mi>n</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math> where <math><mstyle displaystyle="true"><mi>n</mi></mstyle></math> is an integer

Use the form <math><mstyle displaystyle="true"><mi>a</mi><mi>cot</mi><mrow><mo>(</mo><mi>b</mi><mi>x</mi><mo>-</mo><mi>c</mi><mo>)</mo></mrow><mo>+</mo><mi>d</mi></mstyle></math> to find the variables used to find the amplitude, period, phase shift, and vertical shift.

Since the graph of the function <math><mstyle displaystyle="true"><mi>c</mi><mi>o</mi><mi>t</mi></mstyle></math> does not have a maximum or minimum value, there can be no value for the amplitude.

Amplitude: None

The period of the function can be calculated using <math><mstyle displaystyle="true"><mfrac><mrow><mi>π</mi></mrow><mrow><mrow><mo>|</mo><mi>b</mi><mo>|</mo></mrow></mrow></mfrac></mstyle></math> .

Replace <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> with <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> in the formula for period.

The absolute value is the distance between a number and zero. The distance between <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> is <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

The phase shift of the function can be calculated from <math><mstyle displaystyle="true"><mfrac><mrow><mi>c</mi></mrow><mrow><mi>b</mi></mrow></mfrac></mstyle></math> .

Phase Shift: <math><mstyle displaystyle="true"><mfrac><mrow><mi>c</mi></mrow><mrow><mi>b</mi></mrow></mfrac></mstyle></math>

Replace the values of <math><mstyle displaystyle="true"><mi>c</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> in the equation for phase shift.

Phase Shift: <math><mstyle displaystyle="true"><mfrac><mrow><mn>0</mn></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math>

Divide <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

Phase Shift: <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math>

Phase Shift: <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math>

Find the vertical shift <math><mstyle displaystyle="true"><mi>d</mi></mstyle></math> .

Vertical Shift: <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math>

List the properties of the trigonometric function.

Amplitude: None

Period: <math><mstyle displaystyle="true"><mfrac><mrow><mi>π</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math>

Phase Shift: <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> (<math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> to the right)

Vertical Shift: <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math>

The trig function can be graphed using the amplitude, period, phase shift, vertical shift, and the points.

Vertical Asymptotes: <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mfrac><mrow><mi>π</mi><mi>n</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math> where <math><mstyle displaystyle="true"><mi>n</mi></mstyle></math> is an integer

Amplitude: None

Period: <math><mstyle displaystyle="true"><mfrac><mrow><mi>π</mi></mrow><mrow><mn>11</mn></mrow></mfrac></mstyle></math>

Phase Shift: <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> (<math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> to the right)

Vertical Shift: <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math>

Do you know how to Graph -cot(11x)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.

Name | one billion seven hundred eighty-seven million eight hundred forty-eight thousand ninety-five |
---|

- 1787848095 has 8 divisors, whose sum is
**1904491440** - The reverse of 1787848095 is
**5908487871** - Previous prime number is
**17**

- Is Prime? no
- Number parity odd
- Number length 10
- Sum of Digits 57
- Digital Root 3

Name | six hundred forty-three million two hundred thirty-seven thousand seven hundred two |
---|

- 643237702 has 8 divisors, whose sum is
**965010312** - The reverse of 643237702 is
**207732346** - Previous prime number is
**43931**

- Is Prime? no
- Number parity even
- Number length 9
- Sum of Digits 34
- Digital Root 7

Name | one billion eight hundred eighty-six million three hundred seventy-seven thousand two hundred sixty-six |
---|

- 1886377266 has 16 divisors, whose sum is
**3309434400** - The reverse of 1886377266 is
**6627736881** - Previous prime number is
**19**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 54
- Digital Root 9